2017
DOI: 10.1142/s021798491750244x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of bifurcations in a microscopic traffic model accounting for optimal velocity

Abstract: In this paper, a modified microscopic traffic flow model accounting for the optimal velocity has been proposed. Different with previous models, drivers’ response ability and the maximum of accelerations are considered in the term of the optimal velocity. The effect of parameters in the term of the optimal velocity on bifurcations in the rotary traffic is studied here. Besides, the evolvement of bifurcations in the system is calculated by performing numerical simulation experiments. Moreover, the linear stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Wang et al [26] developed a CFS model attributable to vehicle spacing with both lower and upper bounds. Moreover, Wang et al [27] proposed another CFS model incorporating factors of driver's reaction time and maximum acceleration. Different from the above models, Yang et al [28] proposed a new CFS model based on field data.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [26] developed a CFS model attributable to vehicle spacing with both lower and upper bounds. Moreover, Wang et al [27] proposed another CFS model incorporating factors of driver's reaction time and maximum acceleration. Different from the above models, Yang et al [28] proposed a new CFS model based on field data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In general, the complex network can be divided into small world networks, [5] self-similarity ones, [6] regular ones, [7] partly or wholly heterogeneous one. [8] It is capable of modelling real physical or engineering phenomena like traffic flow, [9][10][11][12][13][14][15] the transcription of mRNA, [16] the directional motion of active particles, [17][18][19][20][21][22][23][24][25] etc., which leads the technology networks, [26] social networks, [27] financial network, [28][29][30][31][32][33][34][35][36][37][38][39] biological networks, etc. to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…In order to replicate the evolution of traffic, there is the need for a mathematical modeling of the traffic flow [13][14][15][16][17][18][19][20]. In this regard, scholars have examined a (a) E-mail: poonamr.maths@mdurohtak.ac.in (corresponding author) variety of car-following models [21][22][23][24][25][26] recently, and these models are used to examine the effects of various factors on the traffic flow. But, in comparison to conventional traffic scenarios, it is found that the driver's car-following behavior and the traffic patterns of the following vehicles demonstrated different features.…”
mentioning
confidence: 99%